THE POETICS OF THE CONFLICT IN VASYL STEFANYK’S PROSE: DRAMATIZATION OF THE NOVELLA OR MAKING THE DRAMA EPIC? - Khorob, S. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article researches into the peculiarities of the conflict in Vasyl Stefanyk’s novellas, defines the originality of dramatic categories and elements in the system of the writer’s epic thinking, tracks the processes of dramatization in the narrative discourse of the prosaist, as well as outlines the originality of the authorial ideological-aesthetic consciousness.